PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENGEMBANGAN MODEL DESA KONSERVASI DAN EKOWISATA DI KAWASAN TAMAN NASIONAL MERU BETIRI - Hari Rujito (UPT Penerbitan Universitas Jember)
This study aims to (i) assess the effectiveness of the development of Model Villages Conservation (MDK) and ecotourism in the area around the national park which is a strategy of economic empowerment in the region TNMB and (ii) to compile a